Aplikasi Model Konservasi Levin Pada Pasien Kanker Paru Dengan Efulsi Pleura Di Rumah Sakit Kanker Dharmais Jakarta - Dewi Damayanti (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Background: New cases of lung cancer have increased fivefold in the last decade. Cancer with pleural effusion has a poor prognosis with low life expectancy. Methods: This study is a quantitative study with a single case study approach (instrumental) in this case study discussing only one single case illustrated and then generalizing. This study aims to provide an overview of nursing care in lung cancer patients with pleural eedsi by using Levin conservation approach. The sample of this study were inpatients at Darmais Cancer Hospital Jakarta, April to May 2017. Results: Tropicogenosis identified in Ny. At with Lung ca are: Effective Breathing Disorders, Chronic Pain, Nutrition Deficit and Anxiety. The result of hypothesis / intervention application to tropicognosis showed that hypothesis supports the improvement of welfare and comfort of ca thyroid patient with pleural effusion. Recommendation: The Levin Conservation Model is effective when applied to patients with pulmonary pleural effusion.